Humoral and cellular responses to repeated COVID-19 exposure in multiple sclerosis patients receiving B-cell depleting therapies: a single-center, one-year, prospective study - Alfonso-Dunn, Roberto; Lin, Jerry; Lei, Joyce; Liu, Jiayuan; Roche, Morgan; De Oliveira, Antonia; Raisingani, Amol; Kumar, Anjali; Kirschner, Vanessa; Feuer, Grant; Malin, Michaela; Sadiq, Saud A. (Frontiers in Immunology, 2023)
Multiple sclerosis patients treated with anti-CD20 therapy (aCD20-MS) are considered especially vulnerable to complications from SARS-CoV-2 infection due to severe B-cell depletion with limited viral antigen-specific immunoglobulin production. Therefore, multiple vaccine doses as part of the primary vaccination series and booster updates have been recommended for this group of immunocompromised individuals. Even though much less studied than antibody-mediated humoral responses, T-cell responses play an important role against CoV-2 infection and are induced efficiently in vaccinated aCD20-MS patients. For individuals with such decoupled adaptive immunity, an understanding of the contribution of T-cell mediated immunity is essential to better assess protection against CoV-2 infection. Here, we present results from a prospective, single-center study for the assessment of humoral and cellular immune responses induced in aCD20-MS patients (203 donors/350 samples) compared to a healthy control group (43/146) after initial exposure to CoV-2 spike antigen and subsequent re-challenges. Low rates of seroconversion and RBD-hACE2 blocking activity were observed in aCD20-MS patients, even after multiple exposures (responders after 1st exposure = 17.5%; 2nd exposure = 29.3%). Regarding cellular immunity, an increase in the number of spike-specific monofunctional IFNγ+-, IL-2+-, and polyfunctional IFNγ+/IL-2+-secreting T-cells after 2nd exposure was found most noticeably in healthy controls. Nevertheless, a persistently higher T-cell response was detected in aCD20-MS patients compared to control individuals before and after re-exposure (mean fold increase in spike-specific IFNγ+-, IL-2+-, and IFNγ+/IL-2+-T cells before re-exposure = 3.9X, 3.6X, 3.5X/P< 0.001; after = 3.2X, 1.4X, 2.2X/P = 0.002, P = 0.05, P = 0.004). Moreover, cellular responses against sublineage BA.2 of the currently circulating omicron variant were maintained, to a similar degree, in both groups (15-30% T-cell response drop compared to ancestral). Overall, these results highlight the potential for a severely impaired humoral response in aCD20-MS patients even after multiple exposures, while still generating a strong T-cell response. Evaluating both humoral and cellular responses in vaccinated or infected MS patients on B-cell depletion therapy is essential to better assess individual correlations of immune protection and has implications for the design of future vaccines and healthcare strategies.